Antioxidant and anti-inflammatory potential of spirulina and thymoquinone mitigate the methotrexate-induced neurotoxicity - Alaa Behairy; Ashraf Elkomy; Faten Elsayed; Mohamed M. S. Gaballa; Ahmed Soliman; Mohamed Aboubakr (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
The objective of this study was to investigate whether the neurotoxic effects caused by methotrexate (MTX), a frequently used chemotherapy drug, could be improved by administering Spirulina platensis (SP) and/or thymoquinone (TQ). Seven groups of seven rats were assigned randomly for duration of 21 days. The groups consisted of a control group that was given saline only. The second group was given 500 mg/kg of SP orally; the third group was given 10 mg/kg of TQ orally. The fourth group was given a single IP dose of 20 mg/kg of MTX on the 15 th day of the experiment. The fifth group was given both SP and MTX, the sixth group was given both TQ and MTX, and the seventh group was given SP, TQ, and MTX. After MTX exposure, the study found that AChE inhibition, depletion of glutathione, and increased levels of MDA occurred. MTX also decreased the activity of SOD and CAT, as well as the levels of inflammatory mediators such as IL-1, IL-6, and tumor necrosis factor-α. MTX induced apoptosis in brain tissue. However, when MTX was combined with either SP or TQ, the harmful effects on the body were significantly reduced. This combination treatment resulted in a faster return to normal levels of biochemical, oxidative markers, inflammatory responses, and cell death. In conclusion, supplementation with SP or TQ could potentially alleviate MTX-induced neuronal injury, likely due to their antioxidant, anti-inflammatory, and anti-apoptotic effects.